2015
DOI: 10.1007/s00406-015-0621-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of the corpus callosum unravel pivotal players in the dysfunction of cell signaling, structure, and myelination in schizophrenia brains

Abstract: Schizophrenia is an incurable and debilitating mental disorder that may affect up to 1% of the world population. Morphological, electrophysiological, and neurophysiological studies suggest that the corpus callosum (CC), which is the largest portion of white matter in the human brain and responsible for inter-hemispheric communication, is altered in schizophrenia patients. Here, we employed mass spectrometry-based proteomics to investigate the molecular underpinnings of schizophrenia. Brain tissue samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
60
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 70 publications
12
60
0
3
Order By: Relevance
“…A majority of the encoded proteins were involved in myelin metabolism, thus confirming previous observations made by others [51,52]. Not surprisingly, many OL genes are downregulated in schizophrenia (reviewed in [53][54][55][56] and others), but a number of upregulated genes have also been identified [56]. Among upregulated OL/myelin genes are myelin-associated oligodendrocyte basic protein [54], cyclin D1, and phosphorylated retinoblastoma protein [57]).…”
Section: Discussionsupporting
confidence: 84%
“…A majority of the encoded proteins were involved in myelin metabolism, thus confirming previous observations made by others [51,52]. Not surprisingly, many OL genes are downregulated in schizophrenia (reviewed in [53][54][55][56] and others), but a number of upregulated genes have also been identified [56]. Among upregulated OL/myelin genes are myelin-associated oligodendrocyte basic protein [54], cyclin D1, and phosphorylated retinoblastoma protein [57]).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, studies of silencing and super-expression of proteins showed a crucial role of hnRNP proteins in the myelination of neurons by oligodendrocytes, independently of the indirect regulation of quaking proteins as previously proposed [45,46]. This dysfunction in myelination was related to dysregulation of the synaptic connection [47,48,49]. One of these proteins was HNRNPC, which was found at decreased levels in SCZ patients compared to controls in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Initially, the great majority of the studies were performed in post-mortem brain tissue and it is easy to find large screenings in several brain areas, such as frontal [35] and prefrontal cortex [36]; the corpus callosum [37]; the temporal lobe [38] or the hippocampus [39] (citations as examples, for an extensive review refer to [14]). Later on, other tissues [40,41] or cell populations [42] and body fluids (Tables 1 and 2) or even animal models (e.g.…”
Section: Proteomics Contribution For Schizophrenia's Biomarker Researchmentioning
confidence: 99%